Two Putative α-Helical Domains of Human Immunodeficiency Virus Type 1 Vpr Mediate Nuclear Localization by at Least Two Mechanisms - Kamata, Masakazu (American Society for Microbiology, 2000)
To identify the domains of Vpr that are involved nuclear localization, we transfected HeLa cells with a panel of expression vectors that encode mutant Vpr protein with deletions or substitutions within putative domains. Immunofluorescence staining of transfected cells revealed that wild-type Vpr was localized predominantly in the nucleus and the nuclear envelope and certainly in the cytoplasm. Introduction of substitutions or deletions within αH1 or αH2 resulted, by contrast, in diffuse expression over the entire cell. In addition, double mutations within both of these α-helical domains led to the complete absence of Vpr from nuclei. Next, we prepared HeLa cells that express chimeric proteins which consist of the αH1 and αH2 domains fused individually with green fluorescent protein (GFP) and a Flag tag and extracted them with digitonin and Triton X-100 prior to fixation. Flag-αH1-GFP was detected in the nucleus but not in the cytoplasm, while Flag-αH2-GFP was retained predominantly in the nucleus and in a small amount in the cytoplasm. The immunostaining patterns were almost eliminated by substitutions in each chimeric protein. Thus, it appeared that the two α-helical domains might be involved in nuclear import by binding to certain cellular factors. Taken together, our data suggest that the two putative α-helical domains mediate the nuclear localization of Vpr by at least two mechanisms.